2016
DOI: 10.1097/qai.0000000000000843
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota-Dependent Marker TMAO Is Elevated in Silent Ischemia but Is Not Associated With First-Time Myocardial Infarction in HIV Infection

Abstract: TMAO was elevated in HIV-infected persons with myocardial perfusion defects, but was not associated with first-time MI. Our data question TMAO as a useful biomarker of cardiovascular risk in HIV infection, at least in ART-treated individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 36 publications
0
31
2
1
Order By: Relevance
“…21 Consistent with this, patients commenced on drugs known to modulate tubular function, such as anti-retroviral protease inhibitors 22 and calcineurin inhibitors 23 , may exhibit elevations in plasma TMAO or reduced urinary TMAO clearance. 22,23 Potential cell membrane transporters for TMAO uptake and efflux have been identified. Overexpression of organic cation transporter 2 (Oct2) in…”
Section: Tmao Metabolism In Mammalsmentioning
confidence: 81%
See 1 more Smart Citation
“…21 Consistent with this, patients commenced on drugs known to modulate tubular function, such as anti-retroviral protease inhibitors 22 and calcineurin inhibitors 23 , may exhibit elevations in plasma TMAO or reduced urinary TMAO clearance. 22,23 Potential cell membrane transporters for TMAO uptake and efflux have been identified. Overexpression of organic cation transporter 2 (Oct2) in…”
Section: Tmao Metabolism In Mammalsmentioning
confidence: 81%
“…30 In another HIV cohort, higher plasma TMAO levels were associated with advanced age, reduced kidney function and use of protease inhibitors, but not with coronary artery calcium scores or myocardial infarction. 22 Study of humans with variants of the FMO3 gene could provide opportunities to assess the impact of reduced TMAO production on CV disease.…”
Section: Tmao As a Mediator Of CV Disease: Clinical Datamentioning
confidence: 99%
“…Srinivasa and colleagues found no association between TMAO levels and coronary plaque burden in a group of HIV-infected and uninfected participants, instead finding that levels of its biologic precursor, trimethylamine (TMA), were significantly associated with calcified plaque burden independent of cardiovascular risk factors [18]. Haissman et al similarly did not find differences in TMAO levels between those with and without HIV [19]. However, they did find elevated levels of TMAO in HIV-infected individuals with myocardial perfusion defects on stress testing, which may be consistent with our results as perfusion defects typically occur with coronary stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…These findings prompted an investigation into the association of HIV infection and TMAO levels, which found no association [18]. More recently, Haissman et al similarly found to difference in TMAO levels between HIV-infected and uninfected individuals [19]. We therefore designed a case-control study to further explore the association between coronary atherosclerosis and TMAO levels among participants in the Multicenter AIDS Cohort Study (MACS).…”
Section: Introductionmentioning
confidence: 99%
“…The metabolite Trimethylamine-N-oxide (TMAO), a derivative of Trimethylamine (TMA) that is produced as a waste product of carnitine and choline metabolism by intestinal bacteria, is strongly linked to increased risk for CVD[76-78]. Given that HIV-1 infection is associated with both microbiome changes and with increased CVD risk, a number of recent studies have investigated potential links between TMAO and various aspects of CVD in HIV-1 infected individuals[79-82]. In these pilot studies with relatively small sample sizes, serum and plasma levels of TMAO were not higher in HIV-1 infected study participants compared to uninfected controls and limited evidence for an important role of TMAO in the pathogenesis of coronary heart disease in HIV-1 infected individuals was observed.…”
Section: Linking Alterations In Microbe-associated Metabolites To Hivmentioning
confidence: 99%